The Effect Of Osis Empowerment On Knowledge And Attitude Towards Consuming Balanced Nutritional Food At Smk Plus Almaarif Singosari, Malang Regency: Pengaruh Pemberdayaan OSIS Terhadap Pengetahuan Dan Sikap Mengonsumsi Makanan Bergizi Seimbang Di SMK Plus Almaarif Singosari Kabupaten Malang - Talitha Syahla Aulia; Sri Winarni; Sugianto Hadi (Jurnal Keperawatan Terapan, 2025)
Adolescent dietary behavior today tends to favor fast food and unhealthy diet trends, leading to imbalanced nutritional status. In 2023, the prevalence of malnutrition among adolescents in Indonesia was 7.6% for thin and severely thin, 12.1% overweight, and 4.1% obese. In East Java, adolescent overweight prevalence reached 13.3%, exceeding the national rate. In Malang Regency, the Health Office reported in 2022 that 19.7% of male and 32.9% of female adolescents were obese. This issue of imbalanced nutritional status is also found at SMK Plus Almaarif, due to the absence of a healthy school canteen and students’ low level of understanding regarding balanced nutrition. This study aimed to determine the effect of OSIS empowerment on students’ knowledge and attitudes toward consuming balanced nutritious food at SMK Plus Almaarif Singosari, Malang Regency The research used a quantitative method with a pre-experimental design (one group pre-test and post-test). A total of 60 students from grades X and XI were selected using purposive sampling. The intervention was carried out through seven empowerment steps involving OSIS members as educational agents. The implementation of OSIS empowerment successfully established GENZI Cadres and showed a significant effect of the empowerment intervention on improving students’ knowledge and attitudes, with both showing statistical significance (p = 0.001). OSIS empowerment proved to be statistically effective in enhancing students’ knowledge and attitudes regarding the consumption of balanced nutritious food at SMK Plus Almaarif Singosari.